The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1038/334338a0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective determination of radon in houses

Abstract: In the 1970s it was statistically proved that exposure to radon daughter products caused lung cancer in miners. High concentrations of radon daughters have since been found in houses. Any epidemiological radon study begun today is hampered because relevant exposure data are difficult to obtain owing to the long latency period between exposure and tumour manifestation. Here I present a method for measuring cumulative radon daughter levels, which takes advantage of the fact that the first long-lived radon daught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…The 210 Pb has been accumulated over many years on the surface of solid media (mostly glass), known as surface traps (ST) [5][6][7][8], or in the bulk of porous media (mostly furniture filling sponges), known as volume traps (VT) [9]. Activity of 210 Po can be related to the long-term average indoor radon concentration.…”
Section: Retrospective Assessment Of Radon Exposure (Rare) Techniquesmentioning
confidence: 99%
“…The 210 Pb has been accumulated over many years on the surface of solid media (mostly glass), known as surface traps (ST) [5][6][7][8], or in the bulk of porous media (mostly furniture filling sponges), known as volume traps (VT) [9]. Activity of 210 Po can be related to the long-term average indoor radon concentration.…”
Section: Retrospective Assessment Of Radon Exposure (Rare) Techniquesmentioning
confidence: 99%
“…Long-lived progeny embedded in the surface of glass over time emit alpha particles, which can be counted as an index of the concentration of radon to which the glass has been exposed (24,25). This approach has now been incorporated into several of the case-control studies (26,24-).…”
Section: Radon and Lung Cancer: An Overviewmentioning
confidence: 99%
“…A recently developed glass -based methodology may provide improved estimates for the historical average radon concentrations to which subjects have been exposed indoors (Samuelsson, 1988;Mahaffey et al, 1993 ). This methodology involves assessment of the past average concentrations through measurements of the surface activity on a glass object that has been in a subject's dwellings through the whole or the major part of the exposure period of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Glass objects can be found in the dwellings currently occupied by the subjects or by their next of kin if the subjects are not alive. The surface activity of hard materials like glass is related to the average radon concentrations during several decades due to the long half -life of 210 Pb ( 22.26 years ), a radon progeny found implanted within their surface as a result of the kinetic energy transferred by alpha decay to the radon progeny atoms plating out on surfaces (Lively and Ney, 1987;Samuelsson, 1988 ). An epidemiologic study recently completed in Missouri showed significantly increased risks when radon was measured with surface monitors but not when air measurements were used to assess residential radon exposure, suggesting that the glass -based methodology allowed more accurate estimation of exposure and of the related lung cancer risk (Alavanja et al, 1999).…”
Section: Introductionmentioning
confidence: 99%